Interstate and International Conflicts: Approaches to Regional Security (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article explores the nature of interstate and international conflicts, offering an in-depth analysis of their typologies, causes, and mechanisms of resolution within the framework of international relations.The study examines key theoretical approaches to conflict analysis and provides a comprehensive overview of Uzbekistan’s role in fostering regional cooperation and stability in Central Asia through strategic initiatives and good-neighborly diplomacy.